THE DYNAMIC TRANSITION FROM LIMITED ENGLISH PROFICIENCY INTO ENGLISH PROFICIENCY IN ASSESSING UNIVERSITY STUDENTS’ UNDERSTANDING OF CHEMISTRY CONCEPTS - El-Kilani, Safa Zaid; Kailani, Mohammed Hussein M.R.; Kailani, Zeinab (European Scientific Journal, ESJ, 2013)
Jordanian students study science using their mother tongue Arabic at school; however, they shift into English in studying scientific courses at university. The study investigates if using English in assessing the level of understanding scientific concepts would underestimate the level of freshman’s comprehension for those concepts. The results of the study show that the group of freshman students who had been tested with the Arabic version of SAP (Symbolic Application Particulate) chemistry test did better than the group who got the English version 41%> 38%, without a significant difference at α =.05; the results also show that senior students who had been tested with the English version of the test did better than those who had been tested with the Arabic version 49%> 44%, still without a significant difference at α =.05; the results also show that the two groups of sophomore students (who had been tested with the English version and those who had been tested with Arabic version) got the same average -39% each. The findings of the study show that there is a dynamic transition in students’ ability to comprehend scientific concepts; students became more fluent in understanding scientific concepts at later stages of study. The findings of the study suggests that important decisions related to the academic achievement of freshman students (as acceptance into medical college) should not be based upon assessment in English language content courses at the early stage of students’ academic study.